Dorsiflexion, Plantar-Flexion, and Neutral Ankle Positions During Passive Resistance Assessments of the Posterior Hip and Thigh Muscles - Palmer, Ty B. (J Athl Train, 2015)
CONTEXT: Passive straight-legged–raise (SLR) assessments have been performed with the ankle fixed in dorsiflexion (DF), plantar-flexion (PF), or neutral (NTRL) position. However, it is unclear whether ankle position contributes to differences in the passive resistance measured during an SLR assessment. OBJECTIVE: To examine the influence of ankle position during an SLR on the passive torque, range of motion (ROM), and hamstrings electromyographic (EMG) responses to passive stretch of the posterior hip and thigh muscles. DESIGN: Crossover study. SETTING: Research laboratory. PATIENTS OR OTHER PARTICIPANTS: A total of 13 healthy volunteers (5 men: age = 24 ± 3 years, height = 178 ± 6 cm, mass = 85 ± 10 kg; 8 women: age = 21 ± 1 years, height = 163 ± 8 cm, mass = 60 ± 6 kg). INTERVENTION(S): Participants performed 6 randomly ordered passive SLR assessments involving 2 assessments at each condition, which included the ankle positioned in DF, PF, and NTRL. All SLRs were performed using an isokinetic dynamometer programmed in passive mode to move the limb toward the head at 5°/s. MAIN OUTCOME MEASURE(S): During each SLR, maximal ROM was determined as the point of discomfort but not pain, as indicated by the participant. Passive torque and EMG amplitude were determined at 4 common joint angles (θ) separated by 5° during the final common 15° of ROM for each participant. RESULTS: Passive torque was greater for the DF condition than the NTRL (P = .008) and PF (P = .03) conditions at θ(3) and greater for the DF than NTRL condition (P = .02) at θ(4). Maximal ROM was lower for the DF condition than the NTRL (P = .003) and PF (P < .001) conditions. However, we found no differences among conditions for EMG amplitude (P = .86). CONCLUSIONS: These findings suggest that performing SLRs with the ankle positioned in DF may elicit greater passive torque and lower ROM than SLRs with the ankle positioned in PF or NTRL. The greater passive torque and lower ROM induced by the DF condition possibly were due to increased tension in the neural structures of the proximal thigh.